Pengaruh Mirror Therapy Terhadap Kekuatan Otot Pasien Stroke Non Hemoragik di Rsud Kota Mataram - Pranita, Baiq Dindin Ade (LPPM Institut Teknologi Dan Kesehatan Aspirasi, 2024)
Stroke is a disease or functional impairment of the brain in the form of nerve paralysis due to bleeding (hemorrhagic Stroke) or blockage (non hemorrhagic Stroke) which can cause a decrease in muscle strength on one side of the body that can cause disability so that therapy is needed that can increase muscle strength such as Mirror Therapy. To determine the effect of Mirror Therapy on muscle strength of non-hemorrhagic stroke patients. Pre experiment one group pretest posttest research design. The population is all non-hemorrhagic Stroke patients who experience hemiparesis in Mataram City hospital with a population of 124, sampling using purposive sampling as many as 17. Data collection using MMST observation sheet and analyzed using Wilcoxon Test. Given Mirror Therapy most of the muscle strength in the upper extremities are at grade 2 (wrist & elbow = 70.60% and arm = 58.80%), while the strength of the lower limb muscles are at grade 3 = 58.80%. After the Mirror Therapy intervention, muscle strength in the upper extremities was mostly at grade 3 (wrist = 58.80%, elbow = 70.60%, and arm = 52.90%) while muscle strength in the lower extremities was mostly at grade 4 (ankle = 52.90% and knee = 58.8%). Wilcoxon statistical test results with the analysis of p-value = 0.000 < α 0.05 which means that H0 is rejected which means there is the influence of Mirror Therapy on muscle strength. Mirror Therapy can increase muscle strength in Non Hemorrhagic Stroke patients.